Nutritional potential and viability of edible-winged termites as a sustainable resource for food industrial use - Babirye Khadijah; Ali Ikram; Muhammad Tayyab Arshad (CyTA - Journal of Food)
This review article indicates the untapped edible termites’ nutritional potential and viability as a sustainable resource for future industrial applications. The global quest for sustainable and nutrient-rich food sources has intensified recently. Edible termites are a promising solution to address these challenges. Our study delves into the nutritional composition of edible termites, highlighting their rich protein content, essential amino acids, and valuable micronutrients. We assess their potential as a sustainable alternative for addressing malnutrition and meeting the dietary needs of a growing global population. Regarding industrial applications, we scrutinize the feasibility of incorporating edible termites into food production, their economic viability, scalability, and technological aspects of integrating their products into existing industrial systems. The findings indicate that in the midst of global food insecurity, incorporating edible termites into our industrial practices emerges as a promising avenue for fostering sustainability and resilience in the face of evolving environmental and nutritional challenges. [Figure: see text]